2011
DOI: 10.2136/sssaj2010.0202
|View full text |Cite
|
Sign up to set email alerts
|

Sheep Grazing in a Wheat-Fallow System Affects Dryland Soil Properties and Grain Yield

Abstract: Sheep {Ovis aria L.) grazing, an effective method of controlling weeds and pests in a wheat [Triticum aestivum L.)-fallow system, may affect dryland soil properties and wheat yield. We evaluated the effects of Fallow management for weed concrol and soil water conservation (sheep grazing, herbicide application [chemical], and tillage [mechanical]) and cropping sequence (continuous spring wheat [CSW], spring wheat-fallow [SW-F], and winter wheat-fallow [WW-F]) on soil nutrients and chemical properties in the 0-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 29 publications
6
21
0
Order By: Relevance
“…These results are consistent with studies conducted at the same experimental site (Sainju et al, 2011;Lenssen et al, 2013) and demonstrate the long-term (7-yr) efficacy of an integrated livestock-wheat production system. The results also suggest that grazing-based management provides yields similar to conventional and reduced tillage even in conditions of higher yield potential.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…These results are consistent with studies conducted at the same experimental site (Sainju et al, 2011;Lenssen et al, 2013) and demonstrate the long-term (7-yr) efficacy of an integrated livestock-wheat production system. The results also suggest that grazing-based management provides yields similar to conventional and reduced tillage even in conditions of higher yield potential.…”
Section: Discussionsupporting
confidence: 89%
“…During the first 5 yr of this study, the rotations were CSW and wheat-fallow systems. Our results indicated that sheep-grazed systems resulted in wheat yields equivalent to conventional herbicide-and tillage-based systems (Sainju et al, 2011;Lenssen et al, 2013). This article reports the continuation and modification of the original study with the overall goal of increasing our knowledge base on the effects of crop diversification and grazing on spring wheat yields and quality (test weights and protein content) and weed abundance.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…This was done to include soil residual N so that the concentration of N in the fertilization rates does not exceed the desired amount. Because the soil contained high levels of extractable P and K (Sainju et al 2011), no P and K fertilizers were applied. Immediately after fertilization, spring wheat (cultivar McNeal, Foundation Seed, Montana State University, Bozeman, Montana) was planted in CSW and W-P/B-F using a drill equipped with double disc openers spaced 30 cm apart.…”
Section: Crop Managementmentioning
confidence: 99%